The benefit of combining curcumin, bromelain and harpagophytum to reduce inflammation in osteoarthritic synovial cells - Sybille Brochard; Julien Pontin; Benoit Bernay; Karim Boumediene; Thierry Conrozier; Catherine Baugé (BMC, 2021)
Abstract Background Osteoarthritis (OA) is the most common form of arthritis, affecting millions of people worldwide and characterised by joint pain and inflammation. It is a complex disease involving inflammatory factors and affecting the whole joint, including the synovial membrane. Since drug combination is widely used to treat chronic inflammatory diseases, a similar strategy of designing plant-derived natural products to reduce inflammation in OA joints may be of interest. In this study, we characterised the response of OA synovial cells to lipopolysaccharide (LPS) and investigated the biological action of the combination of curcumin, bromelain and harpagophytum in this original in vitro model of osteoarthritis. Methods Firstly, human synovial cells from OA patients were stimulated with LPS and proteomic analysis was performed. Bioinformatics analyses were performed using Cytoscape App and SkeletalVis databases. Additionally, cells were treated with curcumin, bromelain and harpagophytum alone or with the three vegetal compounds together. The gene expression involved in inflammation, pain or catabolism was determined by RT-PCR. The release of the encoded proteins by these genes and of prostaglandin E2 (PGE2) were also assayed by ELISA. Results Proteomic analysis demonstrated that LPS induces the expression of numerous proteins involved in the OA process in human OA synovial cells. In particular, it stimulates inflammation through the production of pro-inflammatory cytokines (Interleukin-6, IL-6), catabolism through an increase of metalloproteases (MMP-1, MMP-3, MMP-13), and the production of pain-mediating neurotrophins (Nerve Growth Factor, NGF). These increases were observed in terms of mRNA levels and protein release. LPS also increases the amount of PGE2, another inflammation and pain mediator. At the doses tested, vegetal extracts had little effect: only curcumin slightly counteracted the effects of LPS on NGF and MMP-13 mRNA, and PGE2, IL-6 and MMP-13 release. In contrast, the combination of curcumin with bromelain and harpagophytum reversed lots of effects of LPS in human OA synovial cells. It significantly reduced the gene expression and/or the release of proteins involved in catabolism (MMP-3 and -13), inflammation (IL-6) and pain (PGE2 and NGF). Conclusion We have shown that the stimulation of human OA synovial cells with LPS can induce protein changes similar to inflamed OA synovial tissues. In addition, using this model, we demonstrated that the combination of three vegetal compounds, namely curcumin, bromelain and harpagophytum, have anti-inflammatory and anti-catabolic effects in synovial cells and may thus reduce OA progression and related pain.